Electronic Public Procurements Role in Developing Public Services at the Level of Local Authorities - Jaafar, Khadidja (جامعة زيان عاشور بالجلفة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2024)
E-government is a product of the scientific and technological advancements the globe is currently experiencing. It is embodied in the electronic management applied in all central and local state facilities that seek to improve and develop the public service through its electronic transactions in administrative contracts in general and its public procurements in particular.
Keywords: المشتريات العامة -- السلطات المحلية -- الإدارة الرقمية -- الخدمات العامة